Sport system building and long-term athlete development in Canada - Balyi, I. (2001)
The long-term athlete development model, consisting of the FUNdamental, Training to Train, Training to Compete, and Training to Win stages, has become the foundation for British Columbia`s sport system. "SportMap: A Blueprint for Sport Excellence" is a system integration/building tool that encourages cooperation and integration among leaders in the B.C. sport system. Of course, B.C.`s goals cannot be fully realized unless national integration takes place. Other sport-specific, long-term athlete development models (with their collaterals) designed by national and provincial sport organizations, federal and provincial agencies including the Canadian Olympic Association, Sport Canada, and the Coaching Association of Canada could facilitate this process. Alpine Canada Alpin and the Canadian Ski Coaches Federation are leaders in this regard. In 1999, they developed the Alpine Integration Model (AIM), with the help of national and provincial organizations, clubs, and experts from across Canada. This model integrates and sequences Alpine`s athlete development both horizontally and vertically. (The outcome of this process should yield results at the 2010 Winter Olympics). Hopefully the national sport policy will ensure horizontal and vertical integration of the Canadian sport system and will provide leadership and financing for the new system in the near future.